Hydrotalcite-like catalyst as well as preparation method and application thereof

By constructing high-content active Cu+ species in the catalyst and using the hydrotalcite-like catalyst Cu(I)MxAly-LDHs, the problems of low catalytic activity and harsh reaction conditions in the preparation of acetophenone oxidation are solved, and a catalytic effect with high efficiency and high selectivity is achieved.

CN119633829APending Publication Date: 2025-03-18CHINA NAT PETROLEUM CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311191521.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-15
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The prior art has problems such as low catalytic activity, complex catalyst preparation, low selectivity of acetophenone, and harsh reaction conditions in the preparation of acetophenone.

Method used

By constructing high-content active Cu+ species in the catalyst, the hydrotalcite-like catalyst Cu(I)MxAly-LDHs were used, and the catalyst was prepared by adding a reducing agent in situ reduction method to simplify the preparation process and improve the catalytic activity.

Benefits of technology

Under mild reaction conditions, the conversion rate of ethylbenzene reached 95%, the selectivity of acetophenone was 99%, and the catalyst was stable. The effect did not decrease significantly after repeated use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633829A_ABST
    Figure CN119633829A_ABST
Patent Text Reader

Abstract

The invention discloses a hydrotalcite-like catalyst as well as a preparation method and application thereof. According to the invention, a high-content active Cu < + > species is constructed in the catalyst through an in-situ reduction method, and the hydrotalcite-like catalyst Cu (I) MxAly-LDHs is prepared; wherein M is Zn or Mg; x = 1-4, and 2 < = (1 + x) / y < = 5. The preparation method of the catalyst is mild in reaction condition and simple to operate; and the catalyst is used for preparing acetophenone through selective oxidation of ethylbenzene and derivatives thereof, and has high selectivity and yield.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of organic chemical synthesis, and in particular to a hydrotalcite-like catalyst and a preparation method and application thereof. Background Art

[0002] Acetophenone and its derivatives are important organic synthesis intermediates, which can be used as raw materials for synthetic fragrances, drugs and other organic syntheses. Acetophenone can also be used as a solvent for cellulose ethers, cellulose esters, resins, preservatives, rubbers, medicines, dyes, etc. It has the characteristics of high boiling point, stability, pleasant smell, etc., and has broad application prospects.

[0003]

[0004] At present, metal complexes are used in the industry to oxidize ethylbenzene at high temperature in a homogeneous phase to prepare acetophenone (the above reaction formula). For example, JP07196573 discloses a method for synthesizing acetophenone by oxidizing ethylbenzene under the action of oxygen using cobalt cycloalkylcarboxylate or cobalt acetate as a catalyst. The reaction needs to be carried out under high pressure conditions, and the homogeneous catalytic system has the problem of difficulty in recovering the catalyst. CN101759543A discloses a method of obtaining acetophenone by high-temperature oxidation using ethylbenzene as a raw material in the absence of a solvent, oxygen as an oxidant, and a noble metal as a catalyst. The reaction time of this method is long, the reaction yield is not high, and the use of a noble metal catalyst is costly. CN101362680A discloses a method of loading W 10 O 32 + The use of organosilane-modified SBA15 mesoporous molecular sieve photocatalyst has a high yield of acetophenone, but the metal-containing supported catalyst used is a relatively complex catalyst preparation process, and the active components are easily lost during recovery. CN102343280A discloses an IAA-PEI / SiO2-Cu(II) catalyst for catalytic oxidation of ethylbenzene to prepare acetophenone. The method has a high yield, but the supported catalyst used is a relatively complex preparation process, and the active components are easily lost during recovery. CN101759542A discloses the use of mononuclear and binuclear metalloporphyrin-type catalysts to catalytically oxidize ethylbenzene to prepare acetophenone. The method is a homogeneous catalytic process with high catalytic efficiency, but the metalloporphyrin-type homogeneous catalyst is expensive and cannot be recovered and reused.

[0005] The development of heterogeneous catalytic ethylbenzene oxidation process under mild conditions is the development direction of this field. Layered Double Hydroxide (LDHs) is a type of layered double hydroxyl composite metal oxide, and its alkaline properties are conducive to improving the activity of ethylbenzene oxidation system. Moreover, the preparation process of hydrotalcite-like materials is simple, they can be synthesized in large quantities, there is no corrosion to equipment, they can be recycled and reused, and they have the advantages of mild catalytic reaction conditions and low cost. Some literature reports have been published on the application of hydrotalcite-like materials in ethylbenzene oxidation reaction. Li's group (Journal of Industrial and Engineering Chemistry, 2015, 21: 689-695; Chemical Engineering Journal, 2015, 263: 309-316) prepared a methyl silylated MgAl hydrotalcite supported manganese oxide catalyst. In a solvent-free oxidation system, tert-butyl hydroperoxide (TBHP) was added, and the conversion rate of ethylbenzene was 29.5%, and the selectivity of acetophenone was 94.7%; Trakarnpruk et al. (Mendeleev Communications, 2012, 22: 275-277) prepared a series of metal oxide catalysts using hydrotalcite-like materials as precursors, and studied their catalytic performance in ethylbenzene oxidation using TBHP and H2O2 as oxidants. The results showed that MgCuMnAl oxide exhibited the highest catalytic activity. In a system with TBHP as the oxidant, the conversion rate of ethylbenzene was 74%, and the selectivity of acetophenone was 92%. When H2O2 is used as the oxidant, the conversion rate of ethylbenzene is 39% and the selectivity of acetophenone is also 92%. However, the economy and safety of peroxide oxidants are poor; Zhao et al. (Catalysis Communications, 2018, 114: 65-69) prepared a hybrid material of ZnCr-LDH and carbon nanotubes (ZnCr-LDH / CNTs), and reacted under 1MPa oxygen and 130°C for 6h. The conversion rate of ethylbenzene was 54.2%, and the selectivity of acetophenone was 93.7%; Ji et al. (Molecular Catalysis, 2021, 508: 111579) prepared a series of CoNiAl oxides using hydrotalcite-like materials as precursors. In a system with TBHP as an oxidant, Co2Ni1Al1Ox showed better catalytic performance. Under optimized conditions, the conversion rate of ethylbenzene reached 80.0%, and the selectivity of acetophenone was 88.9%; Dai et al. (Catalysis Communications, 2021, 149: 106184) used Cu 2+Cu(II)MgAl hydrotalcites were prepared. When benzonitrile was used as solvent, the selectivity of acetophenone was 95.6% at 120°C. However, the reaction temperature of the catalytic system was relatively high, and the catalytic efficiency needed to be further improved. Jana et al. (Journal of Catalysis, 2007, 247: 214-222) prepared a series of metal-modified MgAl hydrotalcites and investigated their catalytic performance in ethylbenzene oxidation reaction under the condition of direct use of oxygen as oxidant. When Mn-MgAl-LDH (Mg / Al = 4.88) was used as catalyst, the conversion rate of ethylbenzene reached 50.3% and the selectivity of acetophenone reached 96.7% at 135°C. This research group also studied NiAl-LDHs with different anion intercalation (Journal of Catalysis, 2006, 240: 268-274) and found that CO3 2- The intercalated hydrotalcite has a high catalytic activity. Under the above conditions, the conversion rate of ethylbenzene is 47% and the selectivity of acetophenone is 99.3%; Choudhary et al. (Journal of Catalysis, 2004, 227: 257-261) used MnO4-intercalated MgAl-LDH catalyst to catalyze the oxidation of ethylbenzene with molecular oxygen. The conversion rate of ethylbenzene was 22.6% and the selectivity of acetophenone was 98.4%; Zhou et al. prepared a series of Co-containing hydrotalcites (Catalysis Letters, 2022, doi: 10.1007 / s10562-022-04117-w; Applied Catalysis A, General, 2021, 624: 118322) and studied their catalytic performance in the NHPI / O2 system. With Co2Fe-LDH as catalyst and trifluorotoluene as solvent, the conversion rate of ethylbenzene and the selectivity of acetophenone reached 97.6% and 94.9% respectively under the optimized conditions. However, the solvent of this reaction system is expensive and the economic efficiency in practical application is poor.

[0006] Although there have been studies on the application of hydrotalcite-like materials in the oxidation reaction of ethylbenzene and its derivatives, these catalytic systems still have problems such as low catalytic activity, complex catalyst preparation, low acetophenone selectivity, and harsh reaction conditions. Summary of the invention

[0007] An object of the present invention is to provide a hydrotalcite-like catalyst and a preparation method thereof.

[0008] Another object of the present invention is to provide an application of such a hydrotalcite catalyst in the selective oxidation of ethylbenzene and its derivatives to prepare carbonyl compounds, especially in the selective oxidation of ethylbenzene to prepare acetophenone.

[0009] In order to achieve the above objectives, the present invention constructs a high content of active Cu in the catalyst by adding a reducing agent for in-situ reduction. + The preparation process has mild reaction conditions and simple operation; at the same time, the catalyst has high catalytic activity and is used in the selective oxidation of ethylbenzene and its derivatives to prepare acetophenone with high selectivity and yield. The specific technical scheme is as follows:

[0010] In one aspect, the present invention provides a hydrotalcite-like catalyst, specifically a hydrotalcite-like catalyst for preparing carbonyl compounds from ethylbenzene and its derivatives; wherein the hydrotalcite-like catalyst is Cu(I)M x Al y -LDHs;

[0011] Wherein, M is Zn or Mg; x=1-4, and 2≤(1+x) / y≤5.

[0012] The hydrotalcite-like catalyst of the present invention contains a high content of active Cu + species with higher catalytic activity.

[0013] In some specific embodiments of the present invention, preferably, the hydrotalcite-like catalyst is Cu(I)MAl-LDHs.

[0014] In some specific embodiments of the present invention, preferably, in the hydrotalcite-like catalyst, Cu + / Cu 2+ ≥0.3.

[0015] In some specific embodiments of the present invention, preferably, in the hydrotalcite-like catalyst, Cu + / Cu 2+ It is 0.3~0.6.

[0016] Another aspect of the present invention provides a method for preparing the above catalyst, wherein the preparation method comprises the following steps:

[0017] Dissolving a divalent copper salt, a salt corresponding to metal M and an aluminum salt in water to prepare a mixed salt solution;

[0018] Adding Na2CO3 solution and reducing agent into the reactor, and simultaneously dropping NaOH solution and the mixed salt solution into the reactor under stirring;

[0019] When the mixed salt solution is dripped, the dripping is stopped, stirring is continued to generate precipitation, the solid is separated and washed with water until it is neutral, and the catalyst is obtained after drying.

[0020] In the preparation method of the present invention, a high content of active Cu is constructed in the catalyst by adding a reducing agent for in-situ reduction. + Species.

[0021] In some specific embodiments of the present invention, preferably, the divalent copper salt is selected from at least one of divalent copper nitrates, sulfates, chlorides and bromides.

[0022] In some specific embodiments of the present invention, preferably, the divalent copper salt is selected from Cu(NO3)2·3H2O, CuCl2·2H2O, CuBr2 or CuSO4·5H2O.

[0023] In some specific embodiments of the present invention, preferably, the salt corresponding to the metal M is selected from nitrates of Zn or Mg.

[0024] In some specific embodiments of the present invention, preferably, the aluminum salt is a nitrate, more preferably Al(NO3)3·9H2O.

[0025] In some specific embodiments of the present invention, preferably, in the mixed salt solution, the concentrations of the divalent copper salt, the salt corresponding to the metal M and the aluminum salt are independently 0.1 mol / L to 1.0 mol / L. If the ratios of the three are different, the ratios of the three metals in the obtained catalyst are different, and the values ​​of x and y are different.

[0026] In some specific embodiments of the present invention, preferably, the reducing agent is selected from at least one of NaBH4, KBH4, ethanol and methanol.

[0027] By adding a reducing agent, part of the Cu 2+ Reduction to Cu + , thereby preparing high-content active Cu + species, improving catalytic activity.

[0028] In some specific embodiments of the present invention, preferably, the molar ratio of the reducing agent to the divalent copper salt is (0.5-10): 1. After the reducing agent ratio reaches a certain value, further increasing the reducing agent ratio has little effect on the content of monovalent copper, and the molar ratio is more preferably (0.5-1): 1.

[0029] In some specific embodiments of the present invention, preferably, the concentration of the Na2CO3 solution is 1 mol / L to 5.0 mol / L.

[0030] In some specific embodiments of the present invention, preferably, the molar ratio of the amount of Na2CO3 used to the total amount of metal salt is (0.6-10):1.

[0031] In some specific embodiments of the present invention, preferably, the concentration of the NaOH solution is 1.0 mol / L to 3.0 mol / L.

[0032] In some specific embodiments of the present invention, preferably, during the process of adding the solution dropwise, the dropping speed of the solution is controlled to ensure that the pH of the reaction system is maintained at 9.5-10.5.

[0033] In some specific embodiments of the present invention, preferably, after the dropwise addition is stopped, stirring is carried out at 30-80° C. for 6 h to 36 h.

[0034] In some specific embodiments of the present invention, preferably, the drying temperature is 30 to 120° C. and the drying time is 6 h to 24 h.

[0035] In some specific embodiments of the present invention, preferably, the solution is added dropwise at room temperature, in a protective gas atmosphere and under stirring conditions. The protective gas commonly used in the art is an inert gas such as nitrogen or argon, preferably nitrogen.

[0036] In another aspect, the present invention provides use of the above hydrotalcite-like catalysts in the selective oxidation of ethylbenzene and its derivatives to prepare carbonyl compounds.

[0037] Ethylbenzene or its derivatives, the hydrotalcite-like catalyst, N-hydroxyphthalimide (NHPI) and a solvent are added into a reactor and mixed uniformly, and oxygen is introduced to carry out oxidation reaction for 5 hours to 24 hours.

[0038] In some specific embodiments of the present invention, preferably, the solvent is acetonitrile.

[0039] In some specific embodiments of the present invention, preferably, the ethylbenzene or its derivatives are Where R 1 is selected from H, methyl, halogen, methoxy, nitro, ethyl or phenyl, R 2 is selected from methyl, benzyl, phenyl, ethyl or propyl, when R 2 When it is phenyl, two benzene rings are connected to form the ring structure of fluorene; R 2 When it is propyl, the benzene ring and R 2 Different ethylbenzene derivatives have different substituents, different reaction activities, and different oxidation reaction times.

[0040] The halogen atom is selected from fluorine, chlorine, bromine or iodine.

[0041] In some specific embodiments of the present invention, preferably, the molar amount of the N-hydroxyphthalimide is 5% to 20% of ethylbenzene or its derivatives.

[0042] In some specific embodiments of the present invention, preferably, the amount of the hydrotalcite-like catalyst used per mole of ethylbenzene or its derivatives is 10 g to 80 g, more preferably 30 g.

[0043] In some specific embodiments of the present invention, preferably, the temperature of the oxidation reaction is 50-80°C.

[0044] In view of the problems of low catalytic activity, complex catalyst preparation, low acetophenone selectivity, harsh reaction conditions, etc. in the existing selective oxidation of ethylbenzene to acetophenone, the present invention designs and prepares Cu with high catalytic activity and stability. + Heterogeneous catalysts utilize the structure and physicochemical properties of hydrotalcite-like materials and the directional substitution of metal ions to regulate the electronic structure of copper-active oxygen complex intermediates, efficiently achieve the oxidation of aromatic side chain CH, and thus improve catalytic activity and selectivity.

[0045] The hydrotalcite-like catalyst synthesized by the present invention has a conversion rate of ethylbenzene as high as 95% and a selectivity of acetophenone of 99% under mild reaction conditions, and the catalyst effect does not significantly decrease after repeated use, and has good stability; under the same reaction conditions, its comprehensive catalytic performance is significantly better than the related catalytic system in the prior art. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 and Figure 2 The XRD patterns of the hydrotalcite-like catalysts prepared in Examples 1 to 5 and Comparative Examples 1 to 2 are shown.

[0047] Figure 3 This is the Cu 2p XPS spectrum of the hydrotalcite-like catalyst prepared in Example 1.

[0048] Figure 4 This is the Cu 2p XPS spectrum of the hydrotalcite-like catalyst prepared in Example 2.

[0049] Figure 5 This is the Cu 2p XPS spectrum of the hydrotalcite-like catalyst prepared in Example 3.

[0050] Figure 6 This is the Cu 2p XPS spectrum of the hydrotalcite-like catalyst prepared in Example 4.

[0051] Figure 7 This is the Cu 2p XPS spectrum of the hydrotalcite-like catalyst prepared in Example 5.

[0052] Figure 8 This is the Cu 2p XPS spectrum of the hydrotalcite-like catalyst prepared in Comparative Example 1.

[0053] Fig. 9 This is the Cu 2p XPS spectrum of the hydrotalcite-like catalyst prepared in Comparative Example 2. DETAILED DESCRIPTION

[0054] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0055] In the preparation method of the present invention, a high content of active Cu is constructed in the catalyst by an in-situ reduction method. + Species, prepared hydrotalcite-like catalyst Cu(I)M x Al y -LDHs; wherein M is Zn or Mg; x=1 to 4, and 2≤(1+x) / y≤5.

[0056] In some specific embodiments, in the prepared hydrotalcite-like catalyst, Cu + / Cu 2+ ≥0.3, more specifically 0.3-0.6.

[0057] In some specific embodiments, the prepared catalyst is Cu(I)MAl-LDHs.

[0058] The preparation method of the present invention comprises the following steps:

[0059] Dissolving a divalent copper salt, a salt corresponding to metal M and an aluminum salt in water to prepare a mixed salt solution;

[0060] Adding Na2CO3 solution and reducing agent into the reactor, and simultaneously dropping NaOH solution and the mixed salt solution into the reactor under stirring;

[0061] When the mixed salt solution is dripped, the dripping is stopped, stirring is continued to generate precipitation, the solid is separated and washed with water until it is neutral, and the catalyst is obtained after drying.

[0062] In some specific embodiments, the divalent copper salt is selected from at least one of divalent copper nitrate, sulfate, chloride, and bromide, such as Cu(NO3)2·3H2O, CuCl2·2H2O, CuBr2, or CuSO4·5H2O.

[0063] In some specific embodiments, the salt corresponding to the metal M is a nitrate of Zn or Mg, for example, it may be Zn(NO3)2·6H2O or Mg(NO3)2·6H2O.

[0064] In some specific embodiments, the aluminum salt is specifically Al(NO3)3·9H2O.

[0065] In some specific embodiments, in the mixed salt solution, the concentrations of the divalent copper salt, the salt corresponding to the metal M and the aluminum salt are independently 0.1 mol / L to 1.0 mol / L. If the ratios of the three are different, the ratios of the three metals in the obtained catalyst are different, and the values ​​of x and y are different.

[0066] In some specific embodiments, the reducing agent is selected from at least one of NaBH4, KBH4, ethanol, and methanol. By adding the reducing agent, part of the Cu 2+ Reduction to Cu + , thereby preparing high-content active Cu + species, improving catalytic activity.

[0067] In some specific embodiments, the molar ratio of the reducing agent to the divalent copper salt is (0.5-10): 1. After the reducing agent ratio reaches a certain value, further increasing the reducing agent ratio has little effect on the content of monovalent copper, and the molar ratio is more preferably (0.5-1): 1.

[0068] In some specific embodiments, the concentration of the Na2CO3 solution is 1 mol / L to 5.0 mol / L. Preferably, the molar ratio of the amount of Na2CO3 to the total amount of metal salt is (0.6 to 10):1.

[0069] In some specific embodiments, the concentration of the NaOH solution is 1.0 mol / L to 3.0 mol / L. Preferably, during the process of adding the solution dropwise, the speed of adding the solution is controlled to ensure that the pH of the reaction system is maintained at 9.5 to 10.5.

[0070] In some specific embodiments, after the dropwise addition is stopped, stirring is performed at 30-80°C for 6-36 hours; for example, stirring is performed at 65°C for 24 hours. Preferably, the drying temperature is 30-120°C, and the drying time is 6-24 hours; for example, drying is performed at 100°C for 12 hours.

[0071] In some specific embodiments, the solution is added dropwise at room temperature under a protective gas atmosphere and under stirring. The protective gas commonly used in the art is an inert gas such as nitrogen or argon, preferably nitrogen.

[0072] The above hydrotalcite-like catalysts can be used in the selective oxidation of ethylbenzene and its derivatives to prepare carbonyl compounds, and have a very beneficial catalytic effect.

[0073] The specific application steps include: adding ethylbenzene or its derivatives, the hydrotalcite-like catalyst, N-hydroxyphthalimide (NHPI) and a solvent into a reactor and mixing them uniformly, introducing oxygen to carry out oxidation reaction for 5 hours to 24 hours. After the reaction, the conversion rate of the ethylbenzene derivative and the selectivity of the oxidation product are analyzed by gas chromatography.

[0074] The solvent may be acetonitrile. The ethylbenzene or its derivatives may be Where R 1 is selected from H, methyl, halogen, methoxy, nitro, ethyl or phenyl, R 2 is selected from methyl, benzyl, phenyl, ethyl or propyl, when R 2 When it is phenyl, two benzene rings are connected to form the ring structure of fluorene; R 2 When it is propyl, the benzene ring and R 2 Different ethylbenzene derivatives have different substituents, different reaction activities, and different times required for the corresponding oxidation reactions. The halogen atom is selected from fluorine, chlorine, bromine or iodine.

[0075] In some specific embodiments, the molar amount of N-hydroxyphthalimide is 5% to 20% of ethylbenzene or its derivatives.

[0076] In some specific embodiments, the amount of the hydrotalcite-like catalyst used per mole of ethylbenzene or its derivatives is 10 g to 80 g, more preferably 30 g.

[0077] In some specific embodiments, the temperature of the oxidation reaction is 50-80°C.

[0078] The present invention designs and prepares Cu with high catalytic activity and stability + The heterogeneous catalyst uses the structure and physicochemical properties of hydrotalcite-like materials and the directional substitution of metal ions to regulate the electronic structure of the copper-active oxygen complex intermediate, and efficiently realizes the oxidation of the aromatic side chain CH, thereby improving the catalytic activity and selectivity. Under mild reaction conditions, the conversion rate of ethylbenzene is as high as 95%, and the selectivity of acetophenone is 99%. After repeated use, the catalyst effect does not decrease significantly, and the stability is good; under the same reaction conditions, its comprehensive catalytic performance is significantly better than the related catalytic systems in the existing technology.

[0079] The present invention is illustrated below by specific examples. All numerical values ​​specified therein (e.g., temperature, time, concentration, and weight, etc., including the range of each thereof) are generally approximate values ​​that can be appropriately changed (+) or (-) in increments of 0.1 or 1.0. All numerical values ​​specified can be understood as being preceded by the term "about".

[0080] Example 1

[0081] Preparation of Cu(I)ZnAl-LDH(1)

[0082] The preparation of Cu(I)ZnAl-LDH(1) catalyst includes the following steps:

[0083] 1) Prepare 100 mL of a mixed salt solution of Cu(NO3)2·3H2O, Zn(NO3)2·6H2O and Al(NO3)3·9H2O with a concentration of 0.375 mol / L, 100 mL of a Na2CO3 solution with a concentration of 3.0 mol / L, and a sufficient amount of a NaOH solution with a concentration of 2.0 mol / L for use;

[0084] 2) Add the prepared Na2CO3 solution and 0.0375 mol of NaBH4 into a 500 mL round-bottom flask, and simultaneously add the NaOH solution and the mixed salt solution dropwise into the round-bottom flask at room temperature, under nitrogen atmosphere and stirring. Use a pH meter to monitor the pH value of the solution and keep it between 9.5 and 10.5;

[0085] 3) When the mixed salt solution is finished dripping, the dripping is stopped, and the mixture is stirred at a constant temperature of 65° C. for 24 hours, filtered, washed until neutral, and dried at 100° C. to obtain the catalyst Cu(I)ZnAl-LDH(1).

[0086] Example 2

[0087] Preparation of Cu(I)MgAl-LDH(1)

[0088] The preparation of Cu(I)MgAl-LDH(1) catalyst includes the following steps:

[0089] 1) Prepare 100 mL of a mixed solution of CuSO4·5H2O, Mg(NO3)2·6H2O and Al(NO3)3·9H2O with a concentration of 0.375 mol / L, 100 mL of a 5.0 mol / L Na2CO3 solution, and a sufficient amount of a 2.0 mol / L NaOH solution for later use;

[0090] 2) Add the prepared Na2CO3 solution and 0.0375 mol of NaBH4 into a 500 mL round-bottom flask, and simultaneously add the NaOH solution and the mixed salt solution dropwise into the round-bottom flask at room temperature, under nitrogen atmosphere and stirring. Use a pH meter to monitor the pH value of the solution and keep it between 9.5 and 10.5;

[0091] 3) When the mixed salt solution is finished dripping, the dripping is stopped, and the mixture is stirred at a constant temperature of 65° C. for 24 hours, filtered, washed until neutral, and dried at 100° C. to obtain the catalyst Cu(I)MgAl-LDH(1).

[0092] Example 3

[0093] Preparation of Cu(I)MgAl-LDH(2)

[0094] The preparation of Cu(I)MgAl-LDH(2) catalyst includes the following steps:

[0095] 1) Prepare 100 mL of a mixed solution of CuBr2, Mg(NO3)2·6H2O and Al(NO3)3·9H2O with a concentration of 1.0 mol / L, 100 mL of a 1.8 mol / L Na2CO3 solution, and a sufficient amount of a 1.0 mol / L NaOH solution for later use;

[0096] 2) Add the prepared Na2CO3 solution and 0.05 mol KBH4 into a 500 mL round-bottom flask, and simultaneously add the NaOH solution and the mixed salt solution dropwise into the round-bottom flask at room temperature, under nitrogen atmosphere and stirring conditions, and monitor the pH value of the solution with a pH meter to keep it between 9.5 and 10.5;

[0097] 3) When the mixed salt solution is completely added, the addition is stopped, and the mixture is stirred at a constant temperature of 65° C. for 24 hours, filtered, washed until neutral, and dried at 100° C. to obtain the catalyst Cu(I)MgAl-LDH(2).

[0098] Example 4

[0099] Preparation of Cu(I)MgAl-LDH(3)

[0100] The preparation of Cu(I)MgAl-LDH(3) catalyst includes the following steps:

[0101] 1) Prepare 100 mL of a mixed solution of CuCl2·2H2O, Mg(NO3)2·6H2O and Al(NO3)3·9H2O with a concentration of 0.1 mol / L, 100 mL of a 3.0 mol / L Na2CO3 solution, and a sufficient amount of a 3.0 mol / L NaOH solution for later use;

[0102] 2) Add the prepared Na2CO3 solution and 4.6 g of ethanol into a 500 mL round-bottom flask, and simultaneously add the NaOH solution and the mixed salt solution dropwise into the round-bottom flask at room temperature, under nitrogen atmosphere and under stirring conditions, and monitor the pH value of the solution with a pH meter to keep it between 9.5 and 10.5;

[0103] 3) When the mixed salt solution is finished dripping, the dripping is stopped, and the mixture is stirred at a constant temperature of 65° C. for 24 hours, filtered, washed until neutral, and dried at 100° C. to obtain the catalyst Cu(I)MgAl-LDH(3).

[0104] Example 5

[0105] Preparation of Cu(I)ZnAl-LDH(2)

[0106] The preparation of Cu(I)ZnAl-LDH catalyst includes the following steps:

[0107] 1) Prepare 100 mL of a mixed solution of Cu(NO3)2·3H2O, Zn(NO3)2·6H2O and Al(NO3)3·9H2O with a concentration of 0.375 mol / L, 100 mL of a 5.0 mol / L Na2CO3 solution, and a sufficient amount of a 2.0 mol / L NaOH solution for later use;

[0108] 2) Add the prepared Na2CO3 solution, 0.0375 mol KBH4 and 0.19 mol NaBH4 into a 500 mL round-bottom flask, and simultaneously add the NaOH solution and the mixed salt solution dropwise into the round-bottom flask at room temperature, under nitrogen atmosphere and stirring. Use a pH meter to monitor the pH value of the solution and keep it between 9.5 and 10.5;

[0109] 3) When the mixed salt solution is finished dripping, the dripping is stopped, and the mixture is stirred at a constant temperature of 65° C. for 24 hours, filtered, washed until neutral, and dried at 100° C. to obtain the catalyst Cu(I)ZnAl-LDH(2).

[0110] Example 6

[0111] Preparation of Cu(I)Mg4Al-LDH(4)

[0112] The preparation of Cu(I)Mg4Al-LDH(4) catalyst includes the following steps:

[0113] 1) Prepare 100 mL of a mixed solution of 0.1 mol / L Cu(NO3)2·3H2O, 0.4 mol / L Mg(NO3)2·6H2O and 0.1 mol / L Al(NO3)3·9H2O, 100 mL of a 1.0 mol / L Na2CO3 solution, and 3.0 mol / L NaOH solution for later use;

[0114] 2) Add the prepared Na2CO3 solution and 0.01 mol NaBH4 into a 500 mL round-bottom flask, and simultaneously add the NaOH solution and the mixed salt solution dropwise into the round-bottom flask at room temperature, under nitrogen atmosphere and stirring. Use a pH meter to monitor the pH value of the solution and keep it between 9.5 and 10.5;

[0115] 3) When the mixed salt solution is finished dripping, the dripping is stopped, and the mixture is stirred at a constant temperature of 65° C. for 24 hours, filtered, washed until neutral, and dried at 100° C. to obtain the catalyst Cu(I)Mg4Al-LDH(4).

[0116] Comparative Example 1

[0117] Preparation of Cu(II)ZnAl-LDH

[0118] To illustrate the Cu + The catalytic performance of the hydrotalcite catalyst was studied. A Cu(II)ZnAl-LDH catalyst without adding a reducing agent was prepared, comprising the following steps:

[0119] 1) Prepare 100 mL of a mixed solution of Cu(NO3)2·3H2O, Zn(NO3)2·6H2O and Al(NO3)3·9H2O with a concentration of 0.375 mol / L, 100 mL of a 3.0 mol / L Na2CO3 solution, and a sufficient amount of a 2.0 mol / L NaOH solution for later use;

[0120] 2) Add the prepared Na2CO3 solution into a 500 mL round-bottom flask, and mix the NaOH solution and the Cu-containing 2+ The salt mixture solution was simultaneously added dropwise to the above round-bottom flask, and the pH value of the solution was monitored using a pH meter to maintain it between 9.5 and 10.5;

[0121] 3) When the mixed salt solution is finished dripping, the dripping is stopped, and the mixture is stirred at a constant temperature of 65° C. for 24 hours, filtered, washed until neutral, and dried at 100° C. to obtain the catalyst Cu(II)ZnAl-LDH.

[0122] Comparative Example 2

[0123] Preparation of Cu(II)MgAl-LDH

[0124] A Cu(II)MgAl-LDH catalyst without adding a reducing agent was prepared, comprising the following steps:

[0125] 1) Prepare 100 mL of a mixed solution of Cu(NO3)2·3H2O, Mg(NO3)2·6H2O and Al(NO3)3·9H2O with a concentration of 0.375 mol / L, 100 mL of a 3.0 mol / L Na2CO3 solution, and a sufficient amount of a 2.0 mol / L NaOH solution for later use;

[0126] 2) Add the prepared Na2CO3 solution into a 500 mL round-bottom flask, and mix the NaOH solution and the Cu-containing 2+ The salt mixture solution was simultaneously added dropwise to the above round-bottom flask, and the pH value of the solution was monitored using a pH meter to maintain it between 9.5 and 10.5;

[0127] 3) When the mixed salt solution is finished dripping, the dripping is stopped, and the mixture is stirred at a constant temperature of 65° C. for 24 hours, filtered, washed until neutral, and dried at 100° C. to obtain the catalyst Cu(II)MgAl-LDH.

[0128] Comparative Example 3

[0129] Preparation of Mg2Al-LDH

[0130] The preparation of Mg2Al-LDH catalyst includes the following steps:

[0131] 1) Prepare 100 mL of a mixed solution of 0.4 mol / L Mg(NO3)2·6H2O and 0.2 mol / L Al(NO3)3·9H2O, 100 mL of a 3.0 mol / L Na2CO3 solution, and a sufficient amount of a 2.0 mol / L NaOH solution for later use;

[0132] 2) Add the prepared Na2CO3 solution into a 500 mL round-bottom flask, and mix the NaOH solution and Mg-containing solution at room temperature, nitrogen atmosphere and stirring. 2+ The salt mixture solution was simultaneously added dropwise to the above round-bottom flask, and the pH value of the solution was monitored using a pH meter to maintain it between 9.5 and 10.5;

[0133] 3) When the mixed salt solution is finished dripping, the dripping is stopped, and the mixture is stirred at a constant temperature of 65° C. for 24 hours, filtered, washed until neutral, and dried at 100° C. to obtain the catalyst MgAl-LDH.

[0134] Comparative Example 4

[0135] Preparation of Zn2Al-LDH

[0136] The preparation of Zn2Al-LDH catalyst includes the following steps:

[0137] 1) Prepare 100 mL of a mixed solution of 0.4 mol / L Zn(NO3)2·6H2O and 0.2 mol / L Al(NO3)3·9H2O, 100 mL of a 3.0 mol / L Na2CO3 solution, and a sufficient amount of a 2.0 mol / L NaOH solution for later use;

[0138] 2) Add the prepared Na2CO3 solution into a 500 mL round-bottom flask, and mix the NaOH solution and Zn-containing solution at room temperature, nitrogen atmosphere and stirring. 2+ The salt mixture solution was simultaneously added dropwise to the above round-bottom flask, and the pH value of the solution was monitored using a pH meter to maintain it between 9.5 and 10.5;

[0139] 3) When the mixed salt solution is finished dripping, the dripping is stopped, and the mixture is stirred at a constant temperature of 65° C. for 24 hours, filtered, washed until neutral, and dried at 100° C. to obtain the catalyst Zn2Al-LDH.

[0140] Figure 1 and Figure 2 The XRD patterns of the hydrotalcite-like catalysts prepared in Examples 1 to 5 and Comparative Examples 1 to 2 show that the prepared materials all have a hydrotalcite-like structure.

[0141] Figure 3 to Figure 9 The Cu 2p XPS spectra of the hydrotalcite-like catalysts prepared in Examples 1 to 5 and Comparative Examples 1 to 2 are shown. It can be seen that the addition of a reducing agent during the preparation process can increase the Cu content in the hydrotalcite-like material structure. + Combined with their catalytic performance in ethylbenzene oxidation reaction, in CuMgAl and CuZnAl systems, their catalytic activity increases with Cu + Increases with the increase of quantity.

[0142] Table 1 shows the Cu content of the catalyst samples prepared in Examples 1 to 6 and Comparative Examples 1 to 4 obtained based on XPS analysis. + / Cu 2+ ratio.

[0143] Table 1

[0144] sample <![CDATA[Cu + / With 2+ ]]> <![CDATA[S BET (m 2 / g)]]> Example 1 Cu(I)ZnAl-LDH(1) 0.48 72.2 Example 2 Cu(I)MgAl-LDH(1) 0.33 86.2 Example 3 Cu(I)MgAl-LDH(2) 0.53 99.0 Example 4 Cu(I)MgAl-LDH(3) 0.59 86.6 Example 5 Cu(I)ZnAl-LDH(2) 0.32 55.7 Example 6 <![CDATA[Cu(I)Mg4Al-LDH(4)]]> 0.42 100.2 Comparative Example 1 Cu(II)ZnAl-LDH 0.19 30.4 Comparative Example 2 Cu(II)MgAl-LDH 0.06 73.2 Comparative Example 3 <![CDATA[Mg2Al-LDH]]> —— 75.9 Comparative Example 4 <![CDATA[Zn2Al-LDH]]> —— 86.8

[0145] Examples 7-14 are applications of the catalyst prepared in the present invention in ethylbenzene oxidation reactions.

[0146] Example 7

[0147] 1 mmol of ethylbenzene, 30 mg of CuZnAl-LDH (1) catalyst, 0.15 mmol of NHPI and 3 mL of acetonitrile solvent were added into a reactor and mixed uniformly. The temperature was raised to 80° C. and oxygen was introduced under normal pressure to react for 12 h. The reaction liquid was analyzed by gas chromatography. The conversion rate of ethylbenzene was 95%, and the selectivity of the product acetophenone was >99%.

[0148] Example 8

[0149] 1 mmol of ethylbenzene, 10 mg of CuMgAl-LDH (1) catalyst, 0.15 mmol of NHPI and 3 mL of acetonitrile solvent were added into a reactor and mixed uniformly. The temperature was raised to 80° C. and oxygen was introduced under normal pressure to react for 12 h. The reaction liquid was analyzed by gas chromatography. The conversion rate of ethylbenzene was 74%, and the selectivity of the product acetophenone was >99%.

[0150] Example 9

[0151] 1 mmol of ethylbenzene, 30 mg of CuMgAl-LDH (2) catalyst, 0.15 mmol of NHPI and 3 mL of acetonitrile solvent were added into a reactor and mixed uniformly. The temperature was raised to 80° C. and oxygen was introduced under normal pressure to react for 12 h. The reaction liquid was analyzed by gas chromatography. The conversion rate of ethylbenzene was 84% ​​and the selectivity of the product acetophenone was >99%.

[0152] Example 10

[0153] 2 mmol of ethylbenzene, 30 mg of CuMgAl-LDH (3) catalyst, 0.15 mmol of NHPI and 3 mL of acetonitrile solvent were added into a reactor and mixed evenly. The temperature was raised to 80° C. and oxygen was introduced under normal pressure to react for 12 h. The reaction liquid was analyzed by gas chromatography. The conversion rate of ethylbenzene was 78%, and the selectivity of the product acetophenone was >99%.

[0154] Embodiment 11

[0155] 1 mmol of ethylbenzene, 30 mg of CuZnAl-LDH (2) catalyst, 0.2 mmol of NHPI and 3 mL of acetonitrile solvent were added into a reactor and mixed uniformly. The temperature was raised to 80° C. and oxygen was introduced under normal pressure to react for 12 h. The reaction liquid was analyzed by gas chromatography. The conversion rate of ethylbenzene was 92%, and the selectivity of the product acetophenone was >99%.

[0156] Example 12

[0157] 1 mmol of ethylbenzene, 80 mg of CuZnAl-LDH (2) catalyst, 0.05 mmol of NHPI and 3 mL of acetonitrile solvent were added into a reactor and mixed uniformly. The temperature was raised to 80° C. and oxygen was introduced under normal pressure to react for 12 h. The reaction liquid was analyzed by gas chromatography. The conversion rate of ethylbenzene was 88%, and the selectivity of the product acetophenone was >99%.

[0158] Embodiment 13

[0159] 1 mmol of ethylbenzene, 30 mg of CuZnAl-LDH (2) catalyst, 0.15 mmol of NHPI and 3 mL of acetonitrile solvent were added into a reactor and mixed uniformly. The temperature was raised to 50° C. and oxygen was introduced under normal pressure to react for 12 h. The reaction liquid was analyzed by gas chromatography. The conversion rate of ethylbenzene was 58%, and the selectivity of the product acetophenone was >99%.

[0160] Embodiment 14

[0161] 1 mmol of ethylbenzene, 30 mg of CuMg4Al-LDH (4) catalyst, 0.15 mmol of NHPI and 3 mL of acetonitrile solvent were added into a reactor and mixed uniformly. The temperature was raised to 50° C. and oxygen was introduced under normal pressure to react for 12 h. The reaction liquid was analyzed by gas chromatography. The conversion rate of ethylbenzene was 76%, and the selectivity of the product acetophenone was >99%.

[0162] Comparative Example 5

[0163] 1 mmol of ethylbenzene, 30 mg of Cu(II)ZnAl-LDH catalyst, 0.15 mmol of NHPI and 3 mL of solvent acetonitrile were added into a reactor and mixed evenly. The temperature was raised to 80° C. and oxygen was introduced under normal pressure to react for 12 hours. The reaction liquid was analyzed by gas chromatography. The conversion rate of ethylbenzene was 79% and the selectivity of the product acetophenone was >99%.

[0164] Comparative Example 6

[0165] 1 mmol of ethylbenzene, 30 mg of Cu(II)MgAl-LDH catalyst, 0.15 mmol of NHPI and 3 mL of solvent acetonitrile were added into a reactor and mixed evenly. The temperature was raised to 80° C. and oxygen was introduced under normal pressure to react for 12 hours. The reaction liquid was analyzed by gas chromatography. The conversion rate of ethylbenzene was 49% and the selectivity of the product acetophenone was >99%.

[0166] Comparative Example 7

[0167] 1 mmol of ethylbenzene, 30 mg of Mg2Al-LDH catalyst, 0.15 mmol of NHPI and 3 mL of solvent acetonitrile were added into a reactor and mixed evenly. The temperature was raised to 80°C, and oxygen was introduced under normal pressure to react for 12 hours. The reaction liquid was analyzed by gas chromatography. The conversion rate of ethylbenzene was 35%, and the selectivity of the product acetophenone was >99%.

[0168] Comparative Example 8

[0169] 1 mmol of ethylbenzene, 30 mg of Zn2Al-LDH catalyst, 0.15 mmol of NHPI and 3 mL of solvent acetonitrile were added into a reactor and mixed evenly. The temperature was raised to 80°C, and oxygen was introduced under normal pressure to react for 12 hours. The reaction liquid was analyzed by gas chromatography. The conversion rate of ethylbenzene was 41%, and the selectivity of the product acetophenone was >99%.

[0170] Table 2 shows the catalytic performance data of the ethylbenzene oxidation reaction in Examples 7 to 14 and Comparative Examples 5 to 8.

[0171] Table 2

[0172]

[0173]

[0174] The data in Table 2 show that compared with the Cu-free Mg2Al-LDH and Zn2Al-LDH catalysts, the Cu-containing catalysts have significantly higher catalytic activity, indicating that the Cu species has catalytic activity in the ethylbenzene oxidation reaction. The activities of the prepared Cu(I)ZnAl-LDH(1) and Cu(I)ZnAl-LDH(2) catalysts are significantly higher than those of the corresponding Cu(II)ZnAl-LDH; the activities of the prepared Cu(I)MgAl-LDH(1) and Cu(I)MgAl-LDH(2) catalysts are significantly higher than those of the corresponding Cu(II)MgAl-LDH. This indicates that the Cu in the catalyst structure + The activity of species is higher than that of Cu 2+ The above results show that the Cu-containing + The catalyst can catalyze the ethylbenzene oxidation reaction efficiently.

[0175] Examples 15-21 are the results of oxidation reactions of ethylbenzene derivatives as reactants

[0176] Embodiment 15

[0177] 1 mmol of 2-bromoethylbenzene, 30 mg of CuZnAl-LDH (1) catalyst, 0.15 mmol of NHPI and 3 mL of acetonitrile solvent were added into a reactor and mixed uniformly. The temperature was raised to 80° C. and oxygen was introduced under normal pressure to react for 5 hours. The product structure and content were analyzed by gas chromatography-mass spectrometry. The conversion rate of 2-bromoethylbenzene was 96%, and the selectivity of the product 2-bromoacetophenone was 94%.

[0178]

[0179] Example 16

[0180] 1 mmol of p-ethylanisole, 30 mg of CuZnAl-LDH (1) catalyst, 0.15 mmol of NHPI and 3 mL of acetonitrile solvent were added into a reactor and mixed uniformly. The temperature was raised to 80° C. and oxygen was introduced under normal pressure to react for 10 hours. The product structure and content were analyzed by gas chromatography-mass spectrometry. The conversion rate of p-ethylanisole was 95%, and the selectivity of the product 4-methoxyacetophenone was 99%.

[0181]

[0182] Embodiment 17

[0183] 1 mmol of 1,2,3,4-tetralin, 30 mg of CuZnAl-LDH (1) catalyst, 0.15 mmol of NHPI and 3 mL of acetonitrile solvent were added into a reactor and mixed uniformly. The temperature was raised to 80° C. and oxygen was introduced under normal pressure to react for 10 hours. The product structure and content were analyzed by gas chromatography-mass spectrometry. The conversion rate of 1,2,3,4-tetralin was 92%, and the selectivity of the product 1-tetralone was 92%.

[0184]

[0185] Embodiment 18

[0186] 1 mmol of toluene, 30 mg of CuZnAl-LDH (1) catalyst, 0.15 mmol of NHPI and 3 mL of acetonitrile solvent were added into a reactor and mixed uniformly. The temperature was raised to 80° C. and oxygen was introduced under normal pressure to react for 10 h. The product structure and content were analyzed by gas chromatography-mass spectrometry. The toluene conversion rate was 96% and the selectivity of the product benzaldehyde was 56%.

[0187]

[0188] Embodiment 19

[0189] 1 mmol of p-nitroethylbenzene, 30 mg of CuZnAl-LDH (1) catalyst, 0.15 mmol of NHPI and 3 mL of acetonitrile solvent were added into a reactor and mixed uniformly. The temperature was raised to 80° C. and oxygen was introduced under normal pressure to react for 12 h. The product structure and content were analyzed by gas chromatography-mass spectrometry. The conversion rate of p-nitroethylbenzene was 84%, and the selectivity of the product p-nitroacetophenone was >99%.

[0190]

[0191] Embodiment 20

[0192] 1 mmol of fluorene, 30 mg of CuZnAl-LDH (1) catalyst, 0.15 mmol of NHPI and 3 mL of acetonitrile solvent were added into a reactor and mixed evenly. The temperature was raised to 80° C. and oxygen was introduced under normal pressure to react for 24 hours. The product structure and content were analyzed by gas chromatography-mass spectrometry. The conversion rate of fluorene was 91%, and the selectivity of the product fluorenone was >99%.

[0193]

[0194] Embodiment 21

[0195] 1 mmol of cyclohexene, 30 mg of CuZnAl-LDH (1) catalyst, 0.15 mmol of NHPI and 3 mL of acetonitrile solvent were added into a reactor and mixed uniformly. The temperature was raised to 80° C. and oxygen was introduced under normal pressure to react for 12 h. The product structure and content were analyzed by gas chromatography-mass spectrometry. The conversion rate of cyclohexene was 95%, and the selectivity of the product cyclohexene-1-ol was 90%.

[0196]

[0197] Embodiment 22

[0198] Reusability of catalyst

[0199] The reaction liquid after the reaction in Example 7 was filtered to obtain the catalyst CuZnAl-LDH (1) after one use, which was washed with ethyl acetate and dried at 100° C. for 12 hours to obtain the recovered catalyst CuZnAl-LDH (1). The process of repeated use of the recovered catalyst was the same as that of Example 7. The catalyst after the reaction was recovered and reused again. The results of repeated use 5 times are shown in Table 3. It can be seen that the selectivity of acetophenone was maintained above 99%, and the conversion rate of ethylbenzene did not decrease significantly. This shows that the prepared catalyst has good stability.

[0200] Table 3

[0201] Repetitions first Second time The third time Fourth Fifth Ethylbenzene conversion 95% 93% 94% 95% 93% Acetophenone selectivity 99% 99% 99% 99% 99%

[0202] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A hydrotalcite-like catalyst, wherein: The hydrotalcite-like catalyst is Cu(I)M x Al y -LDHs; Wherein, M is Zn or Mg; x=1-4, and 2≤(1+x) / y≤5.

2. The hydrotalcite-like catalyst according to claim 1, wherein The hydrotalcite-like catalyst is Cu(I)MAl-LDHs.

3. The hydrotalcite-like catalyst according to claim 1 or 2, wherein: In the hydrotalcite-like catalyst, Cu + / Cu 2+ ≥0.

3.

4. The hydrotalcite-like catalyst according to claim 3, wherein In the hydrotalcite-like catalyst, Cu + / Cu 2+ It is 0.3~0.

6.

5. A method for preparing the hydrotalcite-like catalyst according to any one of claims 1 to 4, wherein: The preparation method comprises the following steps: Dissolving a divalent copper salt, a salt corresponding to metal M and an aluminum salt in water to prepare a mixed salt solution; Adding Na2CO3 solution and reducing agent into the reactor, and simultaneously dropping NaOH solution and the mixed salt solution into the reactor under stirring; When the mixed salt solution is dripped, the dripping is stopped, stirring is continued to generate precipitation, the solid is separated and washed with water until it is neutral, and the catalyst is obtained after drying.

6. The preparation method according to claim 5, wherein: The divalent copper salt is selected from at least one of divalent copper nitrates, sulfates, chlorides and bromides.

7. The preparation method according to claim 5, wherein: The salt corresponding to the metal M is selected from nitrates of Zn or Mg.

8. The preparation method according to claim 5, wherein: The aluminum salt is nitrate.

9. The preparation method according to claim 5, wherein: In the mixed salt solution, the concentrations of the divalent copper salt, the salt corresponding to the metal M and the aluminum salt are independently 0.1 mol / L to 1.0 mol / L.

10. The preparation method according to claim 5, wherein: The reducing agent is selected from at least one of NaBH4, KBH4, ethanol and methanol.

11. The preparation method according to claim 5, wherein: The molar ratio of the reducing agent to the divalent copper salt is (0.5-10):

1.

12. The preparation method according to claim 5, wherein: The concentration of the Na2CO3 solution is 1 mol / L to 5.0 mol / L; the molar ratio of the amount of Na2CO3 used to the total amount of metal salt is (0.6 to 10):

1.

13. The preparation method according to claim 5, wherein: The concentration of the NaOH solution is 1.0 mol / L to 3.0 mol / L.

14. The preparation method according to claim 5, wherein: During the process of adding the solution dropwise, the dropping speed of the solution is controlled to ensure that the pH of the reaction system is maintained at 9.5-10.

5.

15. Use of the hydrotalcite-like catalyst according to any one of claims 1 to 4 in the selective oxidation of ethylbenzene and its derivatives to prepare carbonyl compounds.

16. The use according to claim 15, wherein: The application comprises the following steps: Ethylbenzene or its derivatives, the hydrotalcite-like catalyst, N-hydroxyphthalimide and a solvent are added into a reactor and mixed uniformly, and oxygen is introduced to carry out oxidation reaction for 5 hours to 24 hours.

17. The use according to claim 16, wherein: The solvent is acetonitrile.

18. The use according to claim 15 or 16, wherein: The ethylbenzene or its derivatives are Where R 1 is selected from H, methyl, halogen, methoxy, nitro, ethyl or phenyl, R 2 is selected from methyl, benzyl, phenyl, ethyl or propyl, when R 2 When it is phenyl, two benzene rings are connected to form the ring structure of fluorene; R 2 When it is propyl, the benzene ring and R 2 Connect to form the ring structure of tetralin.

19. The use according to claim 16, wherein: The molar dosage of the N-hydroxyphthalimide is 5% to 20% of ethylbenzene or its derivatives.

20. The use according to claim 16, wherein: The amount of the hydrotalcite-like catalyst used per mole of ethylbenzene or its derivatives is 10 g to 80 g.

21. The use according to claim 16, wherein: The temperature of the oxidation reaction is 50-80°C.

Citation Information

Patent Citations

  • Hypnone preparation method

    CN101362680A

  • Method for preparing acetophenone by biomimetic catalytic oxidation of ethylbenzene with oxygen

    CN101759542A

  • Method for extracting chalcone from fresh angelica keiskei

    CN101759543A

  • Catalyst for catalyzing oxosynthesis of acetophenone and application thereof

    CN102343280A

  • Production of acetophenone

    JP1995196573A